2019
DOI: 10.5951/jresematheduc.50.4.0362
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Teaching in Conceptually Oriented Mathematics Classrooms Characterized by African American Student Success

Abstract: This article outlines several forms of instructional practice that distinguished middle-grades mathematics classrooms that were organized around conceptually oriented activity and marked by African American students' success on state assessments. We identified these forms of practice based on a comparative analysis of teaching in (a) classrooms in which there was evidence of conceptually oriented instruction and in which African American students performed better than predicted by their previous state assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 0 publications
2
29
0
Order By: Relevance
“…Wilson and colleagues (2019) utilized Gutiérrez' (2002utilized Gutiérrez' ( , 2008 four dimensions of equity within learning environments to develop best practices that create an equitable space within the classroom for marginalized students. They state that when teachers make their expectations explicit, learners are better able to grapple with understanding the content, often coming to an understanding by reconciling the content with their lived experiences (Wilson et. al.…”
Section: Inclusive Mathematics Teaching Practicesmentioning
confidence: 99%
See 4 more Smart Citations
“…Wilson and colleagues (2019) utilized Gutiérrez' (2002utilized Gutiérrez' ( , 2008 four dimensions of equity within learning environments to develop best practices that create an equitable space within the classroom for marginalized students. They state that when teachers make their expectations explicit, learners are better able to grapple with understanding the content, often coming to an understanding by reconciling the content with their lived experiences (Wilson et. al.…”
Section: Inclusive Mathematics Teaching Practicesmentioning
confidence: 99%
“…Through further observation, it was concluded that teachers made expectations explicit across all classrooms observed. However, different approaches to this Working Paper v1.0 | Do NOT share without written consent of lead authors practice were made evident: 1) making expectations explicit via teacher noticing and scaffolding to attend to learner needs to strengthen comprehension and 2) making expectations explicit by attending to the structure of the learner's approach to critical thinking (Wilson et al, 2019). Both approaches allow the teacher to discuss cultural relevance to further aid in learner comprehension, but in different ways.…”
Section: Inclusive Mathematics Teaching Practicesmentioning
confidence: 99%
See 3 more Smart Citations